The egg hunt - Hunt, Roderick (United Kingdom : Oxford university press, 2011)
Biff, Chip, and Kipper search the garden for hidden eggs. They look in different places, find the eggs, and enjoy the fun Easter hunt together.
Children prepare for an egg hunt. They look in the garden, behind bushes and plants. Eggs are found in different hiding spots. The hunt ends happily with everyone enjoying their eggs.
Keywords: English